Correlation between Management Knowledge and Commitment with Board Performance of The Student Education and Training Center - Mawardinur, Mawardinur; Keliat, Pedomanta; Fadhil Rasyid Alfarisyi (Journal Management of Sport, 2022)
This study aims to determine the relationship between management knowledge and commitment to the performance of the management of the Student Education and Training Center (PPLP) in Indonesia. In addition, this study also aims to determine the relationship between management knowledge and commitment together on the performance of PPLP administrators in Indonesia. This research was conducted in North Sumatra from February to June 2022. The research method used is descriptive method with correlation. The sampling technique using proportional random samples totaling 40 people. The analysis technique used is regression technique. The results of this study concluded that: (1) There is a significant relationship between management knowledge and the performance of PPLP administrators in North Sumatra by showing thit = 43.28> ttab 1.68, (2) There is a significant relationship between commitment and the performance of PPLP administrators in North Sumatra by showing thit = 79.3> ttab 1.81, (3) There is a significant relationship together between Management Knowledge and Commitment with the performance of PPLP administrators in North Sumatra by showing thit = 4.94> ttab 1.81.